Pengaruh Media Modifikasi terhadap kemampuan Forehand Tenis meja pada Siswa Ekstrakurikuler di SDN I Ciawijapura - Siti Cahya Nursifa (STKIP Muhammadiyah Kuningan, 2022)
This study focuses on improving the forehand table tennis technique using a bouncing board at Extracurricular SDN I Ciawijapura. The purpose of this study was to determine the improvement of the forehand table tennis technique using a bouncing board for extracurricular students at SDN I Ciawijapura. The researcher used the bouncing board test instrument for 30 seconds (Nurhasan, 2001 : 164-167) to determine the improvement of the forehand technique using the bouncing board. The research method used is a quantitative method. One of the quantitative methods used in this research method is the experimental quantitative method with the research design used